Chronic Health Conditions Among Incoming Canadian Federally Sentenced Women. (January 2017) - Nolan, Amanda M.; Stewart, Lynn A.
Over a 13-month period, health data on all consecutive incoming Canadian federally sentenced women offenders were collected and analyzed ( N = 280). The most common health conditions cited were back pain, head injury, hepatitis C virus (HCV), and asthma. Rates of chronic health problems were generally similar to those of their male offender counterparts, with the notable exception of HCV, which was higher for women. Aboriginal women offenders had particularly high rates of HCV. The study provides valuable information on the self-reported physical health status of federally sentenced women offenders that can be used as a benchmark to examine health trends over time.